MANAGEMENT INFORMATION SYSTEM FOR SOCIAL FUND DISTRIBUTION TO GOVERNMENT AID RECIPIENT STUDENTS - Putra, Fuji Andika; Rapolo, Vyja Tona; Fakhreza, Iudha (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
The emergence of new media, such as websites, is a consequence of advancements in information and communication technology. Online media enables communication without limitations of distance and time. The utilization of websites for information dissemination from the Ministry of Education and Culture of Indonesia to regional education offices and schools serves as an effective solution for information distribution. This study employs the Prototype research method. The results indicate that, first, communication through websites enhances data dissemination effectiveness based on accuracy, timeliness, and information reliability. Second, website utilization improves staff performance by reducing manual tasks. Third, the system provides reports on student beneficiaries, preventing data duplication. According to respondent analysis, the website’s effectiveness in information absorption is categorized as moderate at 44.8%. Additionally, website effectiveness is influenced by the stability of internet networks in different regions, which affects access speed and ease of obtaining information.